Impelementasi Kurikulum Merdeka dalam Pembelajaran Bahasa Indonesia Berbasis Teks pada Siswa Kelas VII Tingkat SMP Negeri di Kecamatan Bolo kabupaten Bima - Lita Nurfatun; Mahsun; Syaiful Musaddat (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This research examines the implementation of the Merdeka Curriculum in text-based Indonesian language learning for class VII students at State Middle Schools in Bolo District, Bima Regency. The Merdeka Curriculum, as the latest innovation in the Indonesian education system, brings significant changes in learning approaches, including in teaching Indonesian. The main aim of this research is to evaluate the effectiveness of implementing this new curriculum, with a special focus on text-based learning which is at the core of Indonesian language teaching.The research method used is a mixed method, combining qualitative and quantitative approaches. The research sample consisted of five state junior high schools in Bolo District, involving 15 Indonesian language teachers and 150 class VII students. Data collection was carried out through classroom observations, in-depth interviews with teachers, student surveys, and analysis of curriculum documents and lesson plans. Qualitative data was analyzed using thematic analysis techniques, while quantitative data was processed using descriptive statistical analysis. Data triangulation was used to increase the validity of research findings.